Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.21203/rs.2.22737/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Predictors of Poor Postoperative Outcomes in Pediatric Surgery Patients in Rural Sub-Saharan Africa

Abstract: Background/Purpose Perioperative complications cause significant pediatric morbidity and mortality in low- and lower middle -income countries. This study investigates factors associated with prolonged length of stay, 90-day readmission and in-hospital mortality among pediatric patients in eastern Ghana. Methods This is a retrospective review of perioperative morbidity and mortality in children <18 years at Eastern Regional Hospital (ERH) in Koforidua, Ghana. All pediatric surgeries performed between January… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
(30 reference statements)
0
0
1
Order By: Relevance
“…In a multicenter, cohort study in low-income countries to measure 30-day postoperative mortality in children aged < 16 years, sex of patients was not determined as a predictor of mortality (14). In contrast to the present study, a signi cant relationship between female sex and perioperative mortality was found in a study conducted in Ghana (15). In a study in California (16), individuals < 21 years old who had cardiac surgery were selected to evaluate the role of gender in cardiovascular outcomes.…”
Section: Discussioncontrasting
confidence: 59%
“…In a multicenter, cohort study in low-income countries to measure 30-day postoperative mortality in children aged < 16 years, sex of patients was not determined as a predictor of mortality (14). In contrast to the present study, a signi cant relationship between female sex and perioperative mortality was found in a study conducted in Ghana (15). In a study in California (16), individuals < 21 years old who had cardiac surgery were selected to evaluate the role of gender in cardiovascular outcomes.…”
Section: Discussioncontrasting
confidence: 59%